A genome‐wide DNA methylation study in azoospermia. (28th August 2013) - Ferfouri, F.; Boitrelle, F.; Ghout, I.; Albert, M.; Molina Gomes, D.; Wainer, R.; Bailly, M.; Selva, J.; Vialard, F.
Summary: The objective of this study was to assess genome‐wide DNA methylation in testicular tissue from azoospermic patients. A total of 94 azoospermic patients were recruited and classified into three groups: 29 patients presented obstructive azoospermia (OA), 26 displayed non‐obstructive azoospermia (NOA) and successful retrieval of spermatozoa by testicular sperm extraction (TESE+) and 39 displayed NOA and failure to retrieve spermatozoa by TESE (TESE−). An Illumina Infinium Human Methylation27 BeadChip DNA methylation array was used to establish a testicular DNA methylation pattern for each type of azoospermic patient. The OA and NOA groups were compared in terms of the relative M ‐value (the log2 ratio between methylated and non‐methylated probe intensities) for each CpG site. We observed significantly different DNA methylation profiles for the NOA and OA groups, with differences at over 9000 of the 27 578 CpG sites; 212 CpG sites had a relative M ‐value >3. The results highlighted 14 testis‐specific genes. Patient clustering with respect to these 212 CpG sites corresponded closely to the clinical classification. The DNA methylation patterns showed that in the NOA group, 78 of the 212 CpG sites were hypomethylated and 134 were hypermethylated (relative to the OA group). On the basis of these DNA methylation profiles, azoospermic patients could be classified as OA or NOA by considering the 212 CpG sites with the greatest methylation differences. Furthermore, we identified genes that may provide insight into the mechanism of idiopathic NOA.